Nonlinear Spectroscopy of Solids at THz Frequencies - Zibod, Soheil (Université d'Ottawa | University of Ottawa, 2024)
This doctoral dissertation focuses on the nonlinear spectroscopy of solids at terahertz frequencies. In this study, the nonlinear propagation of broadband terahertz (THz) pulses through solids is theoretically and experimentally investigated. The experimental observation of a very strong nonlinear response in crystalline quartz in the THz frequency region through THz time-domain spectroscopy (THz-TDS) is reported. A previously developed theoretical model, describing the nonlinear optical interactions, is modified and predicts a very large nonlinear refractive index equal to 5.17 × 10⁻¹⁴ m² W⁻¹. The frequency analysis of the time-domain response reveals a nonlinear refractive index on the order of 10⁻¹³ m² W⁻¹ in addition to a fifth-order nonlinear susceptibility with a negative real part. Moreover, a simple method to model the propagation of a broadband THz pulse in a nonlinear medium with a dispersion of the nonlinear refractive index is presented. This method uses a spectral solution to the wave equation based on Fourier analysis. Using the same model, an expression to extract the nonlinear refractive index dispersion for broadband sources is derived. This model factors out the dependence of the experimental data on the spectral shape of the THz pulse. Furthermore, the model takes the effect of the absorption spectral profile of the material into account. As the next step, the proposed method is applied on the experimental data from the nonlinear spectroscopy of BK7 glass. In addition to its high value of the nonlinear Kerr coefficient equal to 4 × 10⁻¹⁴ m² W⁻¹, BK7 glass is of a great interest due to its absorption profile unique to the borosilicate glass family. Finally, a theoretical study on the relationship between the THz nonlinear refractive index and the THz-induced third-order susceptibility sensed by the optical probe is presented. This analysis explains the scaling factor in the translation of the THz nonlinear refractive index to the optical regime in the phenomena such as terahertz-induced Kerr effect in optical probe setups and terahertz field-induced second-harmonic (TFISH) generation, which is of a great importance for the measurement consistency in different frequency regions.
Keywords: Nonlinear Optics; Solids; Spectroscopy; Terahertz